2022
DOI: 10.1007/s11356-022-19604-1
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of metals by algae from acid mine drainage: a case study of Frongoch Mine (UK)

Abstract: In Frongoch Mine (UK), it is unclear the distribution of metals on indigenous algae and whether these species of algae can accumulate metals. This study aimed to investigate the role of indigenous algae for metal removal from acid mine drainage and understand if metals can be adsorbed on the surface of algae or/and bioaccumulated in algae. A sequential extraction procedure was applied for algae samples collected from acid mine drainage (AMD) water to identify the forms in which metals are found in algae. Conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…was demonstrated in the studies by Say et al, 1977, Say andWhitton 1981;Takamura et al, 1989;Stevens et al, 2001;Skowro ńsky et al, 2002;Gaysina et al, 2009 [61-66]. Although there is lack of data on the species used in our study, it is generally known that algae can hyper-accumulate different metals, including the non-nutrient Pb and Cd, but also the nutritional Cu, Zn, and Fe, with the highest accumulation ratio of Fe, followed by Pb, Cu, Cd, and Zn [67][68][69][70][71][72]. An important statement was made after the experiments conducted by Oberholster et al, 2014, who demonstrated that certain algal species have preferences in elemental bioaccumulation since the accumulated amount of selected metals in the biomass was not strongly dependent on their concentration in the wastewater.…”
Section: Heavy (Hazardous) Metalsmentioning
confidence: 71%
“…was demonstrated in the studies by Say et al, 1977, Say andWhitton 1981;Takamura et al, 1989;Stevens et al, 2001;Skowro ńsky et al, 2002;Gaysina et al, 2009 [61-66]. Although there is lack of data on the species used in our study, it is generally known that algae can hyper-accumulate different metals, including the non-nutrient Pb and Cd, but also the nutritional Cu, Zn, and Fe, with the highest accumulation ratio of Fe, followed by Pb, Cu, Cd, and Zn [67][68][69][70][71][72]. An important statement was made after the experiments conducted by Oberholster et al, 2014, who demonstrated that certain algal species have preferences in elemental bioaccumulation since the accumulated amount of selected metals in the biomass was not strongly dependent on their concentration in the wastewater.…”
Section: Heavy (Hazardous) Metalsmentioning
confidence: 71%
“…In addition, cell walls, nuclei, mitochondria, chloroplasts, and some other parts of the cell may be reinforced by the membrane, which works as a barrier in adapted cells (Chen et al, 2012;Sandau et al, 1996;Tam et al, 1998). In these two stages, some of the metals are bound to the surface, and others may be accumulated within cell due to metals' type and algae growth preference (Du et al, 2022). Surface adsorption is essential since it represents the largest portion of the absorption process (Chojnacka et al, 2005).…”
Section: Mechanism Of Metal Removal By Algaementioning
confidence: 99%
“…Surface adsorption is essential since it represents the largest portion of the absorption process (Chojnacka et al, 2005). Still, the relative importance of surface adsorption may vary depending on the metals and algae (Du et al, 2022). Nevertheless, the complexity of the algae surface makes it possible for various mechanisms to operate simultaneously (Monteiro et al, 2012).…”
Section: Mechanism Of Metal Removal By Algaementioning
confidence: 99%
See 2 more Smart Citations